Frankie and Hazel [videorecording (DVD)] - Plowright, Joan; Barton, Mischa; Uribe, Ingrid; Williams, JoBeth (Feature Films for Families, 2005)
Frankie (Mischa Barton) has studied ballet her whole life. Her grandmother (Joan Plowright) has raised her to be the next prima ballerina, but Frankie has other plans. Meanwhile, Frankie's best friend Hazel has plans of her own with dreams of becoming the town's youngest mayor. Together Frankie and Hazel set out to prove that all it takes is a little kid power to make a big difference.